Investigation of T6 heat treatment on dry sliding wear behaviour of thixoformed A356 composite reinforced with graphene - Salleh, Mohd Shukor; Wakhi Anuar, Nur Farah Bazilah; Omar, Mohd Zaidi; Yahaya, Saifudin Hafiz; Al-Zubaidi, Salah Salman (Penerbit UTeM, 2024)
Improving the wear resistance of graphene reinforced aluminium matrix composites is essential to broaden its application range, notably in high-abrasive environments. Introducing the heat treatment process to graphene reinforced aluminium metal matrix composites potentially resulted in an enhancement in hardness properties and led to an increase in its wear resistance. Thus, this study investigates the impact of the T6 heat treatment on the hardness and wear behaviour of thixoformed GNPs-A356 composites. The GNPs-A356 aluminium composites were produced via the stir casting route in preparation for the subsequent thixoforming process. The feedstock of the composites was reheated to 50% liquid fraction temperature, as identified from the DSC analysis graph, before being rammed into the mould. The thixoformed composites underwent the standard T6 heat-treatment technique. The microstructure of the heat-treated composites shows a formation of spheroidal Si. The addition of GNPs significantly affected the microstructure after the thixoforming process and increased the hardness values from 63 HV for the A356 alloy to 95.39 HV for the thixoformed composite. The following T6 heat treatment process increases the hardness value to 107.45 HV. The volume loss, specific wear rate and average friction of heat-treated GNPs-A356 composites decreased approximately by 28.9 %, 28.7 % and 5.5 %, respectively, compared to A356 alloy. The T6 heat treatment significantly promotes the positive impacts on the properties of hardness and dry sliding wear behaviour of the thixoformed composites.